La política de Enrique Peña Nieto hacia América del Norte: normalización e institucionalización - Santa Cruz, Arturo (El Colegio de México A.C., 2019)
This article aims to present a general overview of the foreign policy of the government of Enrique Peña Nieto with regard to North America, which is of importance due to the process of normalization of cooperation on security with Washington. Likewise, the defense of the relatively recent institutionalization of the economic relationship with the United States and Canada is also significant. To address these issues, a number of analytical concepts that will serve to anchor the narrative are briefly reviewed; the second section examines Mexico’s relationship with the United States, focusing on the two aforementioned thematic areas. The third section briefly reviews the relationship with Canada; the fourth deals succinctly with Mexico’s policy towards North America as a whole and, as a conclusion, presents a brief statement on the future of the region.